Effects of Precursor on Preparation and Properties of Nano-Crystalline Hopcalite Particles - Deraz, N.M.; H. Abd-Elkader, Omar (Asian Journal of Chemistry, 2014)
X-ray diffraction techniques used to determine the structural properties of hopcalite nanoparticles. A mixture of hopcalite and its constituents can be prepared by ceramic method at 800 °C for 5 h. The spinel structure of hopcalite (Cu-Mn-O) confirms by infrared measurements. The copper precursors affect the formation and different properties of hopcalite. Solid state reaction between CuO resulted from copper nitrate with Mn2O3 obtained from manganese carbonate brought about formation of spinel Cu1.5Mn1.5O4 compound with subsequent formation of both Mn2O3 and CuO. On the other hand, using of copper chloride as a source of CuO led to formation of both CuMn2O4 and Mn2O3. The results showed that the change of precursor led to different changes in the structural properties of hopcalite solid including the crystallite size, lattice constant, unit cell volume, X-ray density, the distance between the reacting ions, ionic radii and bond lengths on tetrahedral and octahedral sites involved in the spinel structure.